Hatchet - Paulsen, Gary (Brian's Saga., 1999)
After a plane crash, thirteen-year-old Brian spends fifty-four days in the Canadian wilderness, learning to survive with only the aid of a hatchet given him by his mother, and learning also to survive his parents' divorce.